1963
DOI: 10.1152/jappl.1963.18.6.1294
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green densitometry in flowing blood compensated for background dye

Abstract: Blood is nonhomogeneous; hence, the relationship between light transmission and increasing concentration of dye in whole blood is never the perfect exponential curve predicted by Beer's law. Instead, as the concentration of indocyanine green is increased to high levels (40 mg/liter) the light transmission decreases exponentially toward an asymptote at 6–8% transmission for nearly monochromatic densitometers (half-band width: 13–20 mμ), but at 30–40% for densitometers using light of wide-band width. Consequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

1966
1966
2012
2012

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Calibrations were done by using a control of undyed blood and four different dye concentrations in blood three times during each animal experiment: at the beginning, in the middle, and at the end. These were done on both arterial and venous blood to avoid errors due to differences in oxygen saturation or to differences in hematocrit during the experiment, as was shown to be necessary for precise quantitation (Edwards et al, 1963). The calibration data were analyzed essentially as described previously (Bassingthwaighte et al, 1964) for these densitometers, which provide a Beer's law relationship between detector output and dye concentration over the range 0 to 20 mg per liter.…”
Section: Preparation Of the Animalmentioning
confidence: 99%
See 1 more Smart Citation
“…Calibrations were done by using a control of undyed blood and four different dye concentrations in blood three times during each animal experiment: at the beginning, in the middle, and at the end. These were done on both arterial and venous blood to avoid errors due to differences in oxygen saturation or to differences in hematocrit during the experiment, as was shown to be necessary for precise quantitation (Edwards et al, 1963). The calibration data were analyzed essentially as described previously (Bassingthwaighte et al, 1964) for these densitometers, which provide a Beer's law relationship between detector output and dye concentration over the range 0 to 20 mg per liter.…”
Section: Preparation Of the Animalmentioning
confidence: 99%
“…The calibration data were analyzed essentially as described previously (Bassingthwaighte et al, 1964) for these densitometers, which provide a Beer's law relationship between detector output and dye concentration over the range 0 to 20 mg per liter. The densitometers were set up carefully so that their calibrations were independent of the level of background dye in the blood (Edwards et al, 1963).…”
Section: Preparation Of the Animalmentioning
confidence: 99%
“…EDWARDS [5] and NILSSON [19] found that the calibration curve of a monochromatic densitometer utilizing an interference filter with a narrow pass band (half band width of approximately 13 millimicrons) deviates approximately 3 % from Beers Law 7. A greater deviation from Beers Law results when a filter is used with a wider wave band ( fig.…”
Section: An Approach To Compensation For Nonspecific Effects With Carmentioning
confidence: 99%
“…The magnitude of the deviation varies with the width of the wave band of incident light. It has also been shown that there will be deviation from Beers Law in the calibration curve of a densitometer due to the presence of red blood cells [5]. where I is the transmitted light, I, the incident light, E is a constant for the test substance (dye in this case) at a particular wavelength, c is the concentration of a test substance (dye) and d is the logrithmic relationship between concentration of the dye and the transmitted light.…”
Section: An Approach To Compensation For Nonspecific Effects With Carmentioning
confidence: 99%
“…6 In addition, the right atrial catheter could be connected interchangeably to a saline manometer via a two-way stopcock so that mean right atrial pressures could be read at frequent intervals throughout the experiment. The zero reference level for all pressures was taken at the middorsal-ventral level of the thorax.…”
mentioning
confidence: 99%